Two cases of hemolymphangioma in the thoracic spinal canal and spinal epidural space on MRI: The first report in the literature. Issue 52 (December 2017) - Pan, Xingchen; Dong, Yutong; Yuan, Tingting; Yan, Yuzhu; Tong, Dan
Abstract: Rationale: Hemolymphangioma is a rare, noninvasive benign tumor of mesenchymal origin resulting from malformation of vascular and lymphatic vessels. The incidence of hemolymphangioma in the spinal canal is low. Patient concerns: This report describes 2 patients with a lesion located in the thoracic spinal canal or spinal epidural space, who were misdiagnosed with suspected meningioma or suspected schwannoma, respectively, based on magnetic resonance imaging (MRI). Diagnoses: Hemolymphangioma. Interventions: The application of a surgery was designed to treat the 2 patients. Outcomes: 2 patients stated that symptoms were improved after the operation. Lessons: This report should raise awareness among clinicians that careful image analysis and consideration of patient history and pathology is required for accurate differential diagnosis of hemolymphangioma in the spinal canal and spinal epidural space.